Bank Ownership and Lending Patterns during the 2008-2009 Financial Crisis : Evidence from Latin America and Eastern Europe - Cull, Robert; Martínez Pería, María Soledad (World Bank, Washington, DC, 2013)
This paper examines the impact of bank ownership on credit growth in developing countries before and during the 2008-2009 crisis. Using bank-level data for countries in Eastern Europe and Latin America, it analyzes the growth of banks' total gross loans as well as the growth of corporate, consumer, and residential mortgage loans. Although domestic private banks in Eastern Europe and Latin America contracted their loan growth rates during the crisis, there are differences in foreign and government-owned bank credit growth across regions. In Eastern Europe, foreign bank total lending fell by more than domestic private bank credit. These results are primarily driven by reductions in corporate loans. Furthermore, government-owned banks in Eastern Europe did not act counter-cyclically. The opposite was true in Latin America, where the growth of government-owned banks' corporate and consumer loans during the crisis exceeded that of domestic and foreign banks. Contrary to the case of foreign banks in Eastern Europe, those in Latin America did not fuel loan growth prior to the crisis and did not contract lending at a faster pace than domestic banks during the crisis.